Historical narratives in the Soviet Union and post-Soviet Russia destroying the settled past, creating an uncertain future - Sherlock, Thomas D. (Palgrave Macmillan, 2007)
Establishing a causal link between historical discourse and political change, this important book describes the role of historical discourse in establishing, maintaining, or destroying elite and mass political identities in Soviet and post-Soviet space